Heat Shock Proteins (HSPs) Inducers for Stress Management in Agricultural Crops - Solanki, Shivendu Pratap Singh; Telkar, S. G.; Sharma, Shashikant; Lamo, Kunzang; Dey, Joy Kumar (International Journal of Economic Plants, 2015)
Heat shock proteins (HSP) are expressed in response to various biological stresses, including heat, high pressures, and toxic compounds. It is also one of the most abundant cellular proteins found under non-stress conditions. HSPs are classified into different families and designated by molecular weight in kDa. HSPs 60, 70 and 90: act as molecular chaperons, involving ATP dependent stabilization and folding of proteins and assembly of oligomeric proteins. They can assist in polypeptide transport across membranes into cellular compartments, temporarily bind and stabilize an enzyme at a particular stage in cell development, later releasing the enzyme to become active. Binding of HSP with particular polypeptide within sub cellular compartment avoids denaturation of many proteins at high temperatures.